Assessing faith-based identity in humanitarian governance: A case study of Islamic Relief in Yemen - Nur Diana Izzah (Privietlab, 2026)
Faith-based organizations (FBOs) are increasingly influential in contemporary humanitarian governance. However, limited research has examined how faith-based identities operate within politically fragmented Muslim-majority conflict settings. This study investigates how faith-based identity influences humanitarian governance in Yemen using the case of Islamic Relief. Using a qualitative case study approach, this research analyzes organizational reports, humanitarian publications, institutional documents, academic literature, and human rights reports related to Yemen between 2015 and 2026. This study applies the concepts of humanitarian governance, comparative advantage, and competitive advantage to examine how faith-based identity shapes legitimacy, humanitarian access, donor relations, and operational practices. The findings demonstrate that Islamic Relief’s Islamic identity simultaneously functions as an advantage and a constraint. While it strengthened religious legitimacy, community trust, and access to transnational Muslim donor networks, a shared Muslim identity alone did not guarantee humanitarian access or political legitimacy. Instead, Islamic Relief’s relationships with Western donors, United Nations agencies, and international humanitarian networks generated suspicion among Houthi authorities, contributing to restrictions on and interference with humanitarian operations. This study argues that faith-based legitimacy is context-dependent and politically negotiated, rather than inherently advantageous, within fragmented humanitarian environments.